Mitotic index and pollen viability of Helianthus annuus l., after treatment with Pb(NO3)2 - Dimeska, Gordana; Bilbiloska, Gordana (Macedonian Journal of Ecology and Environment, 2017)
Earlier research indicates that the presence of the lead in the soil demonstrates inhibitory influence on mitosis, meiosis, fertility and the complete growth and development of the plant. Thus this experiment aimed to investigate the influence of known concentrations of lead applied as Pb(NO3)2, on the mitotic cycle and fertility of the sunflower (Helianthus annuus L.). In the process, this cytotoxin was added in various proportionally increasing concentrations (40, 80, 160, 320 mg/kg) in two separate growth phases, in elongation phase and in flowering phase. It has been analysed what was the influence of various concentrations of lead over sunflower production of fertile and sterile pollen grains in correlation with the miotic index. Changes of the mitoitic index (MI) of the treated plants were detected, which was the main indicator for proliferation status of the cell population, and proportionally the increase of lead concentration in the soil resulted in decreasing of fertility and increasing of sterility. The obtained results on the influnce of lead on the cytogenic parameters, and the influence on development of this important agricultural crop, indicate the importance of undertaking activities, greater responsibilities and caution of mankind, being the main factor for waste water release and agricultural activities, i.e. inappropriate use of agricultural chemicals.